Neurocognitive functioning during adolescence: Spanish validation of the Penn Computerized Neurocognitive Battery - Xacobe Fernández‐García; Félix Inchausti; Alicia Pérez‐Albéniz; Javier Ortuño‐Sierra; Raquel Falcó; Eduardo Fonseca‐Pedrero (International Journal of Methods in Psychiatric Research, 2024)
Abstract Objectives The Penn Computerized Neurocognitive Battery ‐ Child Version (PennCNB‐cv) is presented as a brief tool that allows comprehensive and automated assessment of 5 factors (via 14 performance tasks): Executive Control, Episodic Memory, Complex Cognition, Social Cognition, and Sensorimotor Speed. The literature links (dys)functions in these areas with psycho(patho)logical constructs, but evidence is scarce among Spanish‐speaking youth. Therefore, this study aims to validate the PennCNB‐cv in a community sample of Spanish adolescents. Methods After a process of (back)translation and adaptation by bilingual researchers, the PennCNB‐cv was administered in 34 schools. The sample included 1506 students, ages 14–19, 44.28% were male. Preliminary treatment of the data included descriptive and correlational statistics. To provide evidence of structural validity, exploratory and confirmatory factor analyses were performed. Results Results from the exploratory and confirmatory factor analysis showed a four‐factor model (Complex Cognition, Executive Control, Episodic Memory, and Social Cognition) as the most appropriate. These findings provide compelling evidence in favor of the a priori theory that underpinned the development​ of the CNB. Conclusions The study of the psychometric properties showed that the Spanish version of the PennCNB‐cv, seems to be an adequate tool for assessing neurocognitive functioning during adolescence.